2017
DOI: 10.1016/j.pec.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of health coaching in rehabilitation and prevention: A systematic review

Abstract: It is of utmost importance to consider the sustainability already during planning of health coaching interventions. The involvement of the target group and the setting seems to be a promising strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 42 publications
2
54
0
1
Order By: Relevance
“…This increases heterogeneity in intervention components and outcome assessments, as well as the challenge of synthesizing evidence in meta-analysis. Other systematic reviews report a similar heterogeneity (Dejonghe, Becker, Froboese, & Schaller, 2017;Hill, Richardson, & Skouteris, 2015;Wolever et al, 2013). While it was possible to establish whether studies included the key components of health coaching, intervention content was generally poorly reported.…”
Section: Discussionmentioning
confidence: 69%
“…This increases heterogeneity in intervention components and outcome assessments, as well as the challenge of synthesizing evidence in meta-analysis. Other systematic reviews report a similar heterogeneity (Dejonghe, Becker, Froboese, & Schaller, 2017;Hill, Richardson, & Skouteris, 2015;Wolever et al, 2013). While it was possible to establish whether studies included the key components of health coaching, intervention content was generally poorly reported.…”
Section: Discussionmentioning
confidence: 69%
“…Empirical research in Tele-Health Coaching delivered via telephone and online demonstrates it is a key intervention in health behavior change, goal setting and goal achievement. [1][2][3] My critical review of this article is in consonance with current research and recent empirical studies affirming that Telehealth intervention can facilitate goal achievement and have a beneficial effect on the overall mental health, physical health and behavioral health of several multimorbid patient populations. 1,[4][5][6][7][8] Article published January 26, 2018 in the following e-collection issue of the Journal of Medical Internet Research:…”
Section: Resultsmentioning
confidence: 61%
“…Interventions that will be implemented in this study are based on effective health coaching components identified in a systematic review and meta-analysis conducted by the research team prior to this RCT study and other systematic reviews and studies on health coaching in chronic condition management [20,22,25,26]. A twostage intervention for the intervention group will be conducted as described in the following.…”
Section: Description Of the Interventionsmentioning
confidence: 99%
“…In this study, we adapt the definition of health coaching by Wolever and colleagues described as "a patient-centered approach wherein patients at least partially determine their goals, use self-discovery or active learning processes together with content education to work toward their goals, and self-monitor behaviors to increase accountability, all within the context of an interpersonal relationship with a coach" [18]. Although considerable evidence supports the effectiveness of health coaching on quality of life and activities of daily living in other chronic diseases [19][20][21][22][23], findings from the mentioned studies indicate that the effect on stroke survivor's health outcomes varies.…”
Section: Introductionmentioning
confidence: 99%